Preparation method of lead zirconate titanate film of spatial light modulator
The preparation of high-quality lead zirconium titanate films through magnetron sputtering and annealing treatment solves the problem of traditional materials limiting the performance of spatial light modulators, achieving higher electro-optical coefficients, stability and broadening the use environment.
Patent Information
- Application Number
- CN202411789038.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
AI Technical Summary
The preparation of traditional spatial light modulator films uses materials such as lithium niobate, polymer, and barium titanate, which limits the performance of the spatial light modulator, is not conducive to long-term stable operation and is limited in the use environment.
The magnetron sputtering method is used to deposit the lead zirconium titanate target on the substrate to form a uniform and high-quality lead zirconium titanate film, and a dense crystal structure is formed by annealing, and the electrode material is sputtered on the surface of the film to complete the preparation of the spatial light modulator.
The electro-optical coefficient of the spatial light modulator is improved, stability and durability are enhanced, the use environment is broadened, and the modulation amplitude and bandwidth are significantly improved.
Smart Images

Figure CN119615089A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of optoelectronic devices, and in particular to a method for preparing a lead zirconate titanate film of a spatial light modulator. Background Art
[0002] A spatial light modulator (SLM) is an optical device that modulates the amplitude, phase, polarization state and other parameters of the light field by actively controlling liquid crystal molecules or other materials. The spatial light modulator controls its internal units through electrical signals to change the optical properties (such as reflectivity, transmittance, refractive index, etc.), thereby achieving modulation of light waves. Liquid crystal is a commonly used light modulation material, and its molecular arrangement will change under the action of an external electric field, thereby changing the optical properties. Amplitude-type spatial light modulators mainly adjust the intensity of the outgoing light by adjusting the arrangement of liquid crystal molecules; phase-type spatial light modulators achieve wavefront modulation by changing the phase of the light wave.
[0003] In the related technology, the thin film of spatial light modulator is mainly prepared around thin-film lithium niobate, polymer, barium titanate and other materials. The traditional thin-film lithium niobate material has a general electro-optic coefficient, and the modulation amplitude and bandwidth are relatively low, which limits the performance of the spatial light modulator; polymer as a material with a large electro-optic coefficient, although it has certain advantages, is easy to age, has a short service life, and is not conducive to long-term stable operation; although the barium titanate film has a high electro-optic coefficient, its Curie temperature is too low, and the range of use environment is limited, and it cannot work normally in harsh environments such as high temperature. Summary of the invention
[0004] The present application provides a method for preparing a lead zirconate titanate film of a spatial light modulator, which can solve the problem that the traditional spatial light modulator film preparation uses lithium niobate, polymer, and barium titanate materials, which limits the performance of the spatial light modulator, is not conducive to long-term stable operation, and has a limited range of use environments.
[0005] The present invention provides a method for preparing a lead zirconate titanate thin film of a spatial light modulator, which comprises the following steps:
[0006] Using a magnetron sputtering method, a lead zirconate titanate target is deposited onto a pre-prepared substrate to form a lead zirconate titanate film;
[0007] Annealing the substrate on which the lead zirconate titanate film is deposited so that the lead zirconate titanate film forms a dense crystal structure, and after the annealing is completed, naturally cooling the substrate to room temperature;
[0008] The electrode material is sputtered in a selected area on the surface of the formed lead zirconate titanate film to complete the preparation of the spatial light modulator.
[0009] In one embodiment, the method of depositing a lead zirconate titanate target onto a pre-prepared substrate using a magnetron sputtering method to form a lead zirconate titanate film comprises:
[0010] Install the lead zirconate titanate target and substrate to the corresponding positions of the magnetron sputtering system, and adjust the sputtering power, sputtering time, working gas pressure and substrate temperature of the magnetron sputtering system to optimize the sputtering process;
[0011] Start the magnetron sputtering system to make high-energy particles impact the lead zirconate titanate target, sputter out lead zirconate titanate atoms, deposit them on the substrate, and gradually form a uniform lead zirconate titanate film;
[0012] Monitor the growth and quality of the lead zirconate titanate film and stop the sputtering process when the desired film thickness and properties are achieved.
[0013] In one embodiment, before the lead zirconate titanate target and the substrate are installed at corresponding positions of the magnetron sputtering system, the sputtering power, sputtering time, working gas pressure and substrate temperature of the magnetron sputtering system are adjusted to optimize the sputtering process, including:
[0014] Select lead zirconate titanate as the sputtering target, select strontium ruthenate or silicon as the substrate, and ensure the cleanliness and flatness of the substrate surface.
[0015] In one embodiment, during the sputtering process, the sputtering power is set to 180 W, the sputtering time is set to 2 h, the working gas pressure ranges from 0.5 Pa to 5 Pa, and the substrate temperature ranges from 200° C. to 400° C.
[0016] In one embodiment, monitoring the growth and quality of the lead zirconate titanate film and stopping the sputtering process when the desired film thickness and performance are achieved comprises:
[0017] Use a precision thickness gauge to continuously monitor the thickness of the lead zirconate titanate film growth to ensure that the required thickness is achieved;
[0018] The crystal structure and texture of the lead zirconate titanate film were analyzed in real time using an X-ray diffractometer to confirm its crystal quality and phase composition;
[0019] Testing the ferroelectric, dielectric and piezoelectric properties of lead zirconate titanate films;
[0020] The surface morphology of the lead zirconate titanate film was checked using a scanning electron microscope to ensure that there were no cracks or pinholes;
[0021] When the film thickness, crystal structure and performance all reach the predetermined standards, magnetron sputtering is stopped immediately to avoid overgrowth.
[0022] In one embodiment, the precision thickness gauge comprises an ellipsometer or an interferometer.
[0023] In one embodiment, the testing of the ferroelectricity, dielectricity and piezoelectricity of the lead zirconate titanate film comprises:
[0024] Using a ferroelectric material parameter tester, an external electric field is applied to the lead zirconate titanate film, the polarization intensity of the lead zirconate titanate film under the action of the electric field is measured, the relationship between the polarization intensity and the electric field is analyzed, and the ferroelectricity is evaluated;
[0025] Use an impedance analyzer to measure the dielectric constant and dielectric loss of the film;
[0026] The piezoelectric coefficient of the film is measured using a piezoelectric coefficient tester.
[0027] In one embodiment, the substrate on which the lead zirconate titanate film is deposited is annealed to form a dense crystal structure of the film, and after the annealing is completed, the substrate is naturally cooled to room temperature, comprising:
[0028] Controlling the heating rate to ensure that the lead zirconate titanate film is heated evenly and begins to form a crystal structure;
[0029] Keep the temperature at a specific temperature to allow the crystal nuclei to fully form and grow, forming a dense crystal structure;
[0030] After the annealing is completed, the heat source is turned off and the substrate and the lead zirconate titanate film are allowed to cool naturally to room temperature.
[0031] In one embodiment, the step of maintaining the temperature at a specific temperature so that the crystal nuclei are fully formed and grow to form a dense crystal structure comprises:
[0032] Keep the temperature at 800℃ to allow the crystal nuclei to fully form and grow, forming a dense crystal structure.
[0033] In one embodiment, the sputtered electrode material is a gold electrode material.
[0034] The beneficial effects brought by the technical solution provided by the embodiments of the present application include:
[0035] The magnetron sputtering method is used to deposit the lead zirconate titanate target onto the substrate to form a uniform, high-quality lead zirconate titanate film, which replaces traditional materials and improves the electro-optic coefficient; the substrate with the lead zirconate titanate film is annealed to form a dense crystal structure, optimize the crystal quality of the film, improve stability and durability, meet the needs of long-term stable operation, and sputter the electrode material in the selected area on the surface of the lead zirconate titanate film to complete the preparation of the spatial light modulator, improve the modulation amplitude and bandwidth, and broaden the range of use environments. Among them, the lead zirconate titanate film has a high electro-optic coefficient, far exceeding the thin film lithium niobate, which can significantly improve the performance of the spatial light modulator; the lead zirconate titanate material can maintain the stability of its physical and chemical properties under high temperature or chemical environment, is not easy to age, has a long service life, is conducive to long-term stable operation, and solves the problem of easy aging of polymers; the lead zirconate titanate film has a high Curie temperature and can work normally in harsh environments such as high temperature, making up for the defect of the limited use environment of the barium titanate film; through magnetron sputtering and annealing treatment, a dense crystal structure is formed, the film quality and reliability are improved, and high performance requirements are met. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 The present invention is a schematic diagram of a process for preparing a lead zirconate titanate film for a spatial light modulator. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0039] The embodiment of the present application provides a method for preparing a lead zirconate titanate film of a spatial light modulator, which can solve the problem that the traditional spatial light modulator film preparation uses lithium niobate, polymer, and barium titanate materials, which limits the performance of the spatial light modulator, is not conducive to long-term stable operation, and has a limited range of use environments.
[0040] like Figure 1 As shown, the embodiment of the present application provides a method for preparing a lead zirconate titanate film of a spatial light modulator, which comprises the following steps:
[0041] S100: using a magnetron sputtering method, depositing a lead zirconate titanate target onto a pre-prepared substrate to form a lead zirconate titanate film;
[0042] S200: performing annealing treatment on the substrate on which the lead zirconate titanate film is deposited, so that the lead zirconate titanate film forms a dense crystal structure, and after the annealing is completed, naturally cooling the substrate to room temperature;
[0043] S300: sputtering electrode materials in selected areas on the surface of the formed lead zirconate titanate film to complete the preparation of the spatial light modulator.
[0044] In this embodiment, S100 magnetron sputtering deposition uses magnetron sputtering technology to uniformly deposit the lead zirconate titanate target on the substrate. A preliminary film is formed to lay the foundation for subsequent processing. S200 annealing treatment is performed to perform high-temperature annealing on the deposited film to promote the densification of the crystal structure. Improve the crystal quality of the film and enhance performance stability. S300 electrode sputtering sputters electrode materials in selected areas of the film to form a conductive path. The preparation of the lead zirconate titanate film of the spatial light modulator is completed, which has the function of regulating light signals.
[0045] Specifically, the lead zirconate titanate target material is deposited onto the substrate by magnetron sputtering to form a uniform, high-quality lead zirconate titanate film, which replaces traditional materials and improves the electro-optic coefficient; the substrate on which the lead zirconate titanate film is deposited is annealed to form a dense crystal structure, optimize the crystal quality of the film, improve stability and durability, meet the needs of long-term stable operation, and sputter electrode materials in selected areas on the surface of the lead zirconate titanate film to complete the preparation of the spatial light modulator, improve the modulation amplitude and bandwidth, and broaden the range of use environments. Among them, the lead zirconate titanate film has a high electro-optic coefficient, far exceeding the thin film lithium niobate, which can significantly improve the performance of the spatial light modulator; the lead zirconate titanate material can maintain the stability of its physical and chemical properties under high temperature or chemical environment, is not easy to age, has a long service life, is conducive to long-term stable operation, and solves the problem of easy aging of polymers; the lead zirconate titanate film has a high Curie temperature and can work normally in harsh environments such as high temperature, making up for the defect of the limited use environment of the barium titanate film; through magnetron sputtering and annealing treatment, a dense crystal structure is formed, the film quality and reliability are improved, and high performance requirements are met.
[0046] In one embodiment, in S100, the following steps are included:
[0047] S102: installing the lead zirconate titanate target and the substrate to corresponding positions of the magnetron sputtering system, and adjusting the sputtering power, sputtering time, working gas pressure and substrate temperature of the magnetron sputtering system to optimize the sputtering process;
[0048] S103: Start the magnetron sputtering system, so that high-energy particles hit the lead zirconate titanate target, sputter out lead zirconate titanate atoms, deposit on the substrate, and gradually form a uniform lead zirconate titanate film; wherein, when high-energy particles (usually argon ions) hit the lead zirconate titanate target, the target material will be sputtered out. In most cases, the sputtered materials in the magnetron sputtering process are mainly atoms, because sputtering is a physical process, in which high-energy particles hit the target surface, causing the target atoms to obtain sufficient energy and leave the surface. However, under certain conditions, especially when the target compound (such as lead zirconate titanate) undergoes a certain degree of decomposition or chemical reaction during the sputtering process, molecules or molecular clusters are also sputtered out. For a composite oxide target such as lead zirconate titanate, atoms and a small amount of molecules or molecular clusters are sputtered simultaneously during the sputtering process. However, since sputtering is a physical process, and the sputtered materials will experience multiple collisions and scatterings in the process of flying to the substrate, the atoms that are finally deposited on the substrate are mainly atoms, which will gradually gather on the substrate surface and form a uniform lead zirconate titanate film. Therefore, in step S103, what is finally deposited on the substrate and forms a thin film is mainly the atoms of lead zirconate titanate, which gradually form a dense crystal structure through diffusion and rearrangement on the substrate, thereby forming the desired lead zirconate titanate thin film.
[0049] S104: Monitor the growth and quality of the lead zirconate titanate film, and stop the sputtering process when the desired film thickness and performance are achieved.
[0050] In this embodiment, S102 installs the lead zirconate titanate target at the target position of the magnetron sputtering system to ensure that the target surface is clean and free of impurities. Install the substrate on the substrate stage of the system and adjust it to an appropriate distance from the target. Finely adjust the sputtering power to control the number and energy of the sputtered atoms. Set the sputtering time to control the growth thickness of the film. Adjust the working gas pressure to optimize the plasma environment during the sputtering process. Control the substrate temperature to affect the growth rate and crystallization quality of the film. Optimize the sputtering process to ensure the uniformity and quality of the film. By accurately adjusting the parameters, create the best conditions for the sputtering process and improve the deposition efficiency and crystallization quality of the film. S103 starts the magnetron sputtering system to generate a flow of high-energy particles (such as argon ions). The high-energy particles hit the lead zirconate titanate target, causing it to sputter out lead zirconate titanate atoms. The sputtered atoms are deposited on the substrate and gradually form a uniform lead zirconate titanate film. Through the sputtering process, the target material is transferred to the substrate to form the desired film. Achieve uniform deposition of lead zirconate titanate film, laying a good foundation for subsequent annealing and electrode sputtering. S104 uses monitoring equipment to monitor the growth thickness and uniformity of the film in real time. Regularly check the quality of the film, such as crystallinity, surface roughness, etc. When the film reaches the required thickness and performance requirements, stop the sputtering process in time. Ensure that the thickness, uniformity and quality of the film meet application requirements. Through precise monitoring and timely stopping of sputtering, a lead zirconate titanate film that meets the requirements is obtained, providing high-quality substrate materials for subsequent spatial light modulator preparation.
[0051] In one embodiment, before S102, the following steps are included:
[0052] S101: Select lead zirconate titanate as the sputtering target, select strontium ruthenate or silicon as the substrate, and ensure the cleanliness and flatness of the substrate surface.
[0053] In this embodiment, S101 determines to use lead zirconate titanate (PbZrTiO3, referred to as PZT) as the sputtering target because it has good piezoelectric and ferroelectric properties and is suitable for preparing devices such as spatial light modulators. According to application requirements, strontium ruthenate (such as SrRuO3) or silicon (Si) is selected as the substrate material. Strontium ruthenate has good conductivity and lattice matching with PZT, while silicon is widely used because of its wide availability and mature process technology. To ensure that the substrate surface is clean and free of impurities, cleaning, polishing and other processing steps are usually required to remove oil, dust and scratches on the surface to ensure the flatness and cleanliness of the substrate. Provide a high-quality material basis for the sputtering process to ensure the deposition quality and performance of the thin film. By carefully selecting and processing the target material and substrate, a good foundation is laid for the subsequent sputtering process, which helps to improve the adhesion, uniformity and overall performance of the film.
[0054] In one embodiment, in S102, the following steps are included:
[0055] S102-1: During the sputtering process, the sputtering power is set to 180 W, the sputtering time is set to 2 h, the working gas pressure range is 0.5 Pa ~ 5 Pa, and the substrate temperature range is 200 ° C ~ 400 ° C.
[0056] In this embodiment, the sputtering power setting is determined to be 180W, which can ensure sufficient sputtering efficiency at this power while avoiding excessive energy that causes damage to the target material or degradation of the film quality. The sputtering time control is set to 2 hours to ensure that the film reaches the required thickness and uniformity. The working gas pressure is adjusted and controlled in the range of 0.5Pa to 5Pa to optimize the stability of the plasma and the sputtering effect. The substrate temperature management is maintained between 200°C and 400°C. This temperature range helps to improve the crystallization quality and adhesion of the film. By fine-tuning these parameters, the efficient and stable operation of the magnetron sputtering process can be ensured, thereby obtaining high-quality lead zirconate titanate films.
[0057] In one embodiment, in S104, the following steps are included:
[0058] S104-1: Use a precision thickness gauge to continuously monitor the thickness of the lead zirconate titanate film growth to ensure that the required thickness is reached;
[0059] S104-2: Use X-ray diffractometer to analyze the crystal structure and texture of lead zirconate titanate film in real time to confirm its crystal quality and phase composition;
[0060] S104-3: Testing the ferroelectricity, dielectricity and piezoelectricity of lead zirconate titanate films;
[0061] S104-4: Use a scanning electron microscope to check the surface morphology of the lead zirconate titanate film to ensure that there are no cracks or pinholes;
[0062] S104-5: When the film thickness, crystal structure and performance all reach the predetermined standards, magnetron sputtering is stopped immediately to avoid excessive growth.
[0063] In this embodiment, a precision thickness gauge is used for continuous monitoring to ensure that the film reaches the required thickness, and the film thickness is accurately controlled to meet the application requirements. The X-ray diffractometer is used for real-time analysis to confirm the crystallization quality and phase composition of the film to ensure that the film has a good crystal structure and texture. The ferroelectricity, dielectricity and piezoelectricity are tested to ensure that the film performance meets the standards, and the electrical properties of the film are comprehensively evaluated to meet the application requirements. Scanning electron microscope observation ensures that there are no cracks or pinholes on the surface of the film, ensures the surface quality of the film, and improves reliability. Stop magnetron sputtering immediately after reaching the standard to avoid excessive growth, save resources, accurately control the film growth process, and improve production efficiency.
[0064] In one embodiment, in S104-1, the following steps are included:
[0065] S103-1-1: Use an ellipsometer or interferometer to continuously monitor the growth thickness of the lead zirconate titanate film to ensure that the required thickness is reached.
[0066] In this embodiment, the growth thickness of the lead zirconate titanate film is monitored in real time using an ellipsometer or an interferometer. Based on the monitoring results, the growth conditions are adjusted to ensure that the film thickness reaches the required standard. Through continuous monitoring, precise control of the film thickness is achieved. Ensure that the film thickness is uniform, improve the overall quality, and meet application requirements. This step is a key link in the preparation process of lead zirconate titanate film. By accurately controlling the film thickness, a solid foundation is laid for subsequent crystal structure analysis, performance testing and other steps.
[0067] In one embodiment, in S104-3, the following steps are included:
[0068] S104-3-1: Use a ferroelectric material parameter tester to apply an external electric field to the lead zirconate titanate film, measure the polarization intensity of the lead zirconate titanate film under the action of the electric field, analyze the relationship between the polarization intensity and the electric field, and evaluate the ferroelectricity;
[0069] S104-3-2: Use an impedance analyzer to measure the dielectric constant and dielectric loss of the film;
[0070] S104-3-3: Use a piezoelectric coefficient tester to measure the piezoelectric coefficient of the film.
[0071] In this embodiment, in S104-3-1, an external electric field is applied, and a controllable external electric field is applied to the lead zirconate titanate film through a ferroelectric material parameter tester. Measure polarization intensity: record the change in polarization intensity of the film under the action of the electric field. Analyze the relationship between polarization intensity and electric field to evaluate the ferroelectricity of the film. Accurately evaluate the ferroelectric properties of the film and provide key parameters for ferroelectric applications. In S104-3-2, an impedance analyzer is used to measure the dielectric constant and dielectric loss of the film. Understand the dielectric response of the film under an AC electric field to provide data support for dielectric applications. In S104-3-3, a piezoelectric coefficient tester is used to measure the piezoelectric coefficient of the film, that is, the size of the electrical signal generated by the film under mechanical stress or strain. Evaluate the piezoelectric properties of the film and provide key parameters for piezoelectric applications (such as sensors, transducers, etc.). Through the three sub-steps of S104-3, the ferroelectricity, dielectricity and piezoelectricity of the lead zirconate titanate film can be comprehensively evaluated, providing reliable experimental data support for the further application of the film. Ensure the accuracy and reliability of the test results.
[0072] In one embodiment, in S200, the following steps are included:
[0073] S201: Control the heating rate to ensure that the lead zirconate titanate film is heated evenly and begins to form a crystal structure;
[0074] S202: keeping the temperature at a specific temperature so that the crystal nuclei are fully formed and grow to form a dense crystal structure;
[0075] S203: After the annealing is completed, turn off the heat source and allow the substrate and the lead zirconate titanate film to cool naturally to room temperature.
[0076] In this embodiment, annealing is an important step in the preparation process of lead zirconate titanate film, which plays a vital role in optimizing the crystal structure of the film and improving the performance of the film. S201 controls the heating rate by accurately controlling the heating rate of the annealing furnace or heat treatment equipment. Ensure that the lead zirconate titanate film is evenly heated to avoid uneven crystal structure or thermal stress caused by excessive temperature gradient. Begin to form a uniform and fine crystal structure, laying the foundation for further growth of subsequent crystals. S202 sets the annealing furnace or heat treatment equipment to a specific temperature and maintains the temperature for a period of time. Allow the crystal nucleus to fully form and grow, and form a more dense and orderly crystal structure through the diffusion and rearrangement of atoms. Improve the crystallinity of the film, reduce crystal defects, optimize the crystal structure of the film, and thus improve its electrical, mechanical and other properties. S203 After annealing is completed, turn off the heat source and let the substrate and the lead zirconate titanate film cool naturally to room temperature in the annealing furnace or heat treatment equipment. Avoid thermal stress or sudden changes in crystal structure caused by rapid cooling, and ensure that the crystal structure of the film remains stable during the cooling process. The obtained lead zirconate titanate film has a stable crystal structure and good performance, providing a reliable material basis for subsequent applications. Through the S200 annealing step, the crystal structure of the lead zirconate titanate film can be further optimized, and its performance can be improved, providing strong support for the application of the film in the fields of ferroelectric, dielectric, piezoelectric, etc. At the same time, precise annealing process control is also the key to ensure the stability and consistency of film quality.
[0077] In one embodiment, in S202, the following steps are included:
[0078] S202-1: Keep the temperature at 800°C to allow the crystal nuclei to fully form and grow, forming a dense crystal structure.
[0079] In this embodiment, the insulation temperature is 800°C. The purpose of insulation is to allow the crystal nuclei to fully form and grow at this high temperature, and the atoms have enough energy to diffuse and rearrange. Promote the formation of crystal nuclei, and make the existing crystal nuclei gradually grow to form a denser and more ordered crystal structure. Improve the crystallinity of the film and reduce crystal defects. Optimize the crystal structure of the film, thereby improving its physical, chemical and electrical properties. Lay a good foundation for subsequent steps (such as natural cooling after annealing) to ensure the stability and consistency of the film quality. This step is a key link in the preparation process of lead zirconate titanate film. By accurately controlling the insulation temperature, the crystal structure of the film can be accurately controlled, thereby obtaining a film material with excellent performance.
[0080] In one embodiment, in S300, the following steps are included:
[0081] S300-1: Sputtering gold electrode material on a selected area on the surface of the formed lead zirconate titanate film (a selected area on the top of the resonant subsurface) to complete the preparation of the spatial light modulator.
[0082] In this embodiment, gold electrode material is deposited by sputtering technology in selected areas on the surface of the lead zirconate titanate film that has been formed. According to the design requirements of the spatial light modulator, the area where the gold electrode needs to be deposited is accurately selected. Using a sputtering device, the gold target material is sputtered out under the bombardment of high-speed ions or electrons and deposited on the surface of the lead zirconate titanate film. According to the application requirements, the sputtering time and sputtering power are controlled to obtain a gold electrode of the desired shape and size. The electrode preparation of the lead zirconate titanate film in the spatial light modulator is completed, providing a basis for subsequent electrical connection and performance testing. The gold electrode has good conductivity and chemical stability, which can ensure the stability and reliability of the film under electrical operation. Through the S300-1 step, we successfully prepared a gold electrode on the surface of the lead zirconate titanate film, providing a key component for the further assembly and testing of the spatial light modulator. The precise execution of this step is crucial to ensure the performance and stability of the entire spatial light modulator.
[0083] In the description of the present application, it should be noted that the terms "upper", "lower", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. Unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.
[0084] It should be noted that, in this application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.
[0085] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a lead zirconate titanate film for a spatial light modulator, characterized in that: It includes the following steps: Using a magnetron sputtering method, a lead zirconate titanate target is deposited onto a pre-prepared substrate to form a lead zirconate titanate film; Annealing the substrate on which the lead zirconate titanate film is deposited so that the lead zirconate titanate film forms a dense crystal structure, and after the annealing is completed, naturally cooling the substrate to room temperature; The electrode material is sputtered in a selected area on the surface of the formed lead zirconate titanate film to complete the preparation of the spatial light modulator.
2. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 1, characterized in that: The method of using a magnetron sputtering method to deposit a lead zirconate titanate target onto a pre-prepared substrate to form a lead zirconate titanate film comprises: Install the lead zirconate titanate target and substrate to the corresponding positions of the magnetron sputtering system, and adjust the sputtering power, sputtering time, working gas pressure and substrate temperature of the magnetron sputtering system to optimize the sputtering process; Start the magnetron sputtering system to make high-energy particles impact the lead zirconate titanate target, sputter out lead zirconate titanate atoms, deposit them on the substrate, and gradually form a uniform lead zirconate titanate film; Monitor the growth and quality of the lead zirconate titanate film and stop the sputtering process when the desired film thickness and properties are achieved.
3. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 2, characterized in that: Before installing the lead zirconate titanate target and the substrate to the corresponding positions of the magnetron sputtering system, adjusting the sputtering power, sputtering time, working gas pressure and substrate temperature of the magnetron sputtering system to optimize the sputtering process, the method includes: Select lead zirconate titanate as the sputtering target, select strontium ruthenate or silicon as the substrate, and ensure the cleanliness and flatness of the substrate surface.
4. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 2, characterized in that: During the sputtering process, the sputtering power was set to 180 W, the sputtering time was set to 2 h, the working gas pressure ranged from 0.5 Pa to 5 Pa, and the substrate temperature ranged from 200° C. to 400° C.
5. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 2, characterized in that: The method of monitoring the growth and quality of the lead zirconate titanate film and stopping the sputtering process when the desired film thickness and performance are achieved comprises: Use a precision thickness gauge to continuously monitor the thickness of the lead zirconate titanate film growth to ensure that the required thickness is achieved; The crystal structure and texture of the lead zirconate titanate film were analyzed in real time using an X-ray diffractometer to confirm its crystal quality and phase composition; Testing the ferroelectric, dielectric and piezoelectric properties of lead zirconate titanate films; The surface morphology of the lead zirconate titanate film was checked using a scanning electron microscope to ensure that there were no cracks or pinholes; When the film thickness, crystal structure and performance all reach the predetermined standards, magnetron sputtering is stopped immediately to avoid overgrowth.
6. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 5, characterized in that: Precision thickness gauges include ellipsometers or interferometers.
7. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 5, characterized in that: The method for testing the ferroelectricity, dielectricity and piezoelectricity of the lead zirconate titanate film comprises: Using a ferroelectric material parameter tester, an external electric field is applied to the lead zirconate titanate film, the polarization intensity of the lead zirconate titanate film under the action of the electric field is measured, the relationship between the polarization intensity and the electric field is analyzed, and the ferroelectricity is evaluated; Use an impedance analyzer to measure the dielectric constant and dielectric loss of the film; The piezoelectric coefficient of the film is measured using a piezoelectric coefficient tester.
8. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 1, characterized in that: The method comprises: annealing the substrate on which the lead zirconate titanate film is deposited so that the film forms a dense crystal structure, and after the annealing is completed, naturally cooling the substrate to room temperature, comprising: Controlling the heating rate to ensure that the lead zirconate titanate film is heated evenly and begins to form a crystal structure; Keep the temperature at a specific temperature to allow the crystal nuclei to fully form and grow, forming a dense crystal structure; After the annealing is completed, the heat source is turned off and the substrate and the lead zirconate titanate film are allowed to cool naturally to room temperature.
9. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 8, characterized in that: The method of maintaining the temperature at a specific temperature so that the crystal nuclei are fully formed and grow to form a dense crystal structure includes: Keep the temperature at 800℃ to allow the crystal nuclei to fully form and grow, forming a dense crystal structure.
10. The method for preparing a lead zirconate titanate thin film for a spatial light modulator according to claim 1, characterized in that: The sputtered electrode material is gold electrode material.
Citation Information
Cited By
Lead zirconate titanate target material, preparation method thereof and piezoelectric device
CN122102686A